Reconciliation in a Socio‑political Dimension - Мидић, Игнатије (Sabornost - The Theological Year-book, 2015)
A question we are asking ourselves is the following one: how is peace to be realized and maintained among people? We, as members of the Church, are especially interested to know what the role of the Church is in relation to the problem of realization and maintenance of peace. In order to give positive answers to these questions we need, first of all, to identify what causes hostilities and disturbances to happen among people.